Rethinking New Social Movements from a Relational Perspective - Sökmen, Mehmet; Kasapoglu, Aytul (Advances in Social Sciences Research Journal, 2026)
This article aims to reconceptualize new social movements from a relational sociological perspective, replacing outdated typological classifications and identity-centered paradigms. Recent studies on new social movements find the focus on traditional collective identity, organization, and cultural factors insufficient, instead centering on distributed network-based and emotional characteristics. In this context, drawing particularly on the work of relational sociologists like Harrison White, and building upon Bruno Latour's Actor-Network Theory, Iris Marion Young's concept of seriality, and Lauren Berlant's curiel optimism, the article aims to develop a relational sociological Network Intensification Model to analyze current new social movements. The proposed model represents a significant innovation contributing to the existing literature by conceptualizing social movements not as stable collective actors, but as temporary network intensifications arising from serial positioning and sustained by emotional ties. This model highlights the role of not only humans but also non-humans, algorithms, platforms, images, and material objects in the emergence of social movements. Instead of focusing on fixed categories such as “environmental” or “feminist” movements, the model emphasizes degrees of network density, synchronization thresholds, emotional circulation, and algorithmic visibility. Drawing on relational sociological principles and focusing on process analysis rather than typological classifications, the article attempts to contribute to the dynamic and non-anthropocentric ontology of collective action. In this context, the article presents contemporary social movements as cyclical formations that intensify, dissolve, and potentially re-emerge through relational structures. This theoretical work also gains value by offering new methodological and theoretical avenues for examining digitally mediated and emotionally structured forms of movement.